EFL teachers’ perception towards online classroom interaction during covid-19 pandemic - Putri Candra Kusuma; Muhammad Reza Pahlevi; Hilmansyah Saefullah (Universitas PGRI Semarang, 2021)
The spread of Covid-19 is affecting education systems around the world and transform the learning from face-to-face to online learning. Interaction is important pattern to share knowledge between teachers and students. Previous research has said that interaction could also encourage students to master the subject matter. This study aims to describe the EFL teachers’ perception towards classroom interaction during Covid-19 pandemic especially on how the interaction between teacher-student, student-teacher, and student-student synchronously which is assisted by Google Meet. The research method used in this study is descriptive case study and taking data by conducting observation, interview, and documentation. Based on research result, teacher perceive online classroom interaction in balance emotion, exploratory talk tends to be implemented in online classroom interactions, Indirect talk of asking questions is the dominant online classroom interaction.